IMPLEMENTASI PROGRAM PENCEGAHAN PEREDARAN NARKOTIKA OLEH BADAN NARKOTIKA NASIONAL KABUPATEN (BNNK) DI KABUPATEN KARIMUN TAHUN 2021 – 2023 - Gemala, Rifki Wanda; ', Wazni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Prevention of drug trafficking in Indonesia, especially in Karimun Regency, is a matter of concern. Because drugs are a latent danger that drug abuse really needs to be aware of so that it can be handled with various strategies that have been created by the National Narcotics Agency (BNN), but it does not rule out the possibility that there will be several obstacles that occur both internally from the parties handling it and from the perpetrators. drug trafficking itself. The problem with this research is that there is still insufficient/limited implementation of policies and programs implemented by the government in dealing with narcotics trafficking. The purpose of this research is to find out and understand the implementation of the Narcotics Trafficking Prevention Program by the Regency National Narcotics Agency in Karimun Regency 2021-2023 by referring to implementation theory according to George C. Edwards III who explains that communication in activities carried out by BNNK is expected to raise public awareness of the dangers of drugs through socialization. Then there are resources where the roles such as the staff who carry out their respective duties are in accordance with their respective fields, but the institutions that collaborate with BNN, such as the team appointed by the government at the sub-district level, do not perform optimally in their duties in the field. The final part is the disposition based on the attitude of policy implementers related to BNN collaborating with government institutions and civil society in implementing this narcotics distribution and prevention program which has been carried out to the maximum. This research is descriptive qualitative research with the main data sources being primary data and secondary data. The data collection techniques used were interview and documentation techniques. This data analysis technique is Data Reduction, Data Presentation and Conclusion Drawing. The results of this research are that the Karimun Regency Government has carried out programs such as socialization and strategies for preventing and eradicating drug abuse by implementing the Prevention of Eradication of Abuse and Illicit Narcotics Trafficking (P4GN) Program, counseling on the ins and outs of drugs or efforts to monitor, control the production and distribution of drugs in the community. However, there are still factors that hamper this program, such as the role of the community in participating in drug trafficking, and inadequate infrastructure that hinders the program from running. Keywords: Communication, Resources, Disposition.